Stay safe, play safe : a book about safety rules - Seuling, Barbara; Berk, Bernice; Allert, Kathy (New York : Golden Books ; Racine, Wis. : Western Pub. Co., 1985)
Provides safety tips for a variety of outdoor and indoor activities.
3.0
K-3
Keywords: Children's accidents -- Prevention -- Juvenile literature; Safety education -- Juvenile literature; Safety; Safety education -- Fiction; play -- sports